Pengaruh Pengembangan Kurikulum dan Pembentukan Karakter Taruna/i Terhadap Kualitas Pendidikan di Program Diploma Pelayaran - Malik, Djamaludin; Mudiyanto (Universitas Hang Tuah, 2020)
Curriculum development is a process of planning and compiling curriculum by the academic sector or curriculum developer so that the resulting curriculum can be a reference used in achieving national education goals. Character building is the process of providing education and training in the context of increasing knowledge, expertise, skills and shaping the behavior of human resources. The purpose of this study is to explain how much influence the curriculum development and character development of cadets have on the quality of education in the Program Diploma Pelayaran. The methodology of this research is quantitative method, the number of respondents is 171 with the results of the research that the R value is a multiple of 0,947 show evidence of curriculum development and character building have a very strong relationship to the quality of education variables.